Leachate nanofiltration concentrate treatment by advanced electrochemical processes to achieve zero waste discharge: modeling and optimization - Varank, Gamze (ELSEVIER SCIENCE INC, 2020)
The aim of this work is to achieve zero waste discharge in leachate treatment. Advanced electrochemical processes were applied to leachate nanofiltration concentrate formed at the nanofiltration unit of Komurctioda Leachate Treatment Plant. The performance of the electrochemical processes with peroxymonosulfate, peroxydisulfate and hydrogen peroxide addition as oxidants was investigated in the removal of the UV254 parameter-representing recalcitrant organic matterfrom the leachate nanofiltration (NF) concentrate. To design and optimize the process parameters affecting the performance of electro-peroxymonosulfate (EPM), electro-peroxydisulfate (EPD) and electro-Fenton (EF) processes, central composite design (CCD) and response surface methodology (RSM) were applied. Oxidant/chemical oxygen demand ratio, current, pH, and reaction time were selected as independent variables, and the UV254 parameter which is at high concentrations in NF concentrate of leachate was selected as the system's response. By the application of CCD, the regression quadratic model was developed, and the data obtained were analyzed by analysis of variance. Under optimum conditions, the removal efficiencies of the UV254 parameter through EPM, EPD and EF processes were determined as 84.9%, 98.6% and 92.2%, respectively and the operational cost of was found to be 2.2, 3.8 and 4.7 (sic)/m(3) for EPM, EPD and EF processes, respectively All three processes are effective advanced treatment methods for UV254 parameter removal from leachate NF concentrate and RSM is appropriate for designing and optimizing all three processes.
Keywords: Central composite design; Electro-Fenton; Electro-peroxydisulfate; Electro-peroxymonosulfate; Leachate nanofiltration concentrate; UV254 parameter; RESPONSE-SURFACE METHODOLOGY; ADVANCED OXIDATION PROCESSES; MATURE LANDFILL LEACHATE; AQUEOUS-SOLUTIONS; FENTON OXIDATION; BISPHENOL-A; HEAVY-METALS; DEGRADATION; REMOVAL; Engineering; Water Resources